2020
DOI: 10.1016/j.celrep.2020.108173
|View full text |Cite
|
Sign up to set email alerts
|

LET-502/ROCK Regulates Endocytic Recycling by Promoting Activation of RAB-5 in a Distinct Subpopulation of Sorting Endosomes

Abstract: Highlights d Loss of LET-502/ROCK affects endocytic recycling in C. elegans intestine d LET-502 interacts with RAB-5(GDP) and promotes RABX-5 GEF activity toward RAB-5 d RABX-5 and RME-6 activate RAB-5 in spatially distinct endosome subpopulations d LET-502-RABX-5 replenishes RAB-5 in a deep cytosolic subset of endosomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, three putative Rho effectors, formin CYK-1/mDia, LET-502/ROCK, and RTKN- 1/Rhotekin, are known to function in basolateral recycling in the C. elegans intestine, although current models posit that these proteins function independently of RHO-1 in recycling (11, 54, 55). Branched actin formed by Arp2/3 is traditionally considered the relevant F-actin type associated with endosomes, but recycling may require a balance of branched and linear actin for proper function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Rab5 promotes the fusion of nascent endocytic vesicles with early endosomes and fusion between early endosomes, so it is often used as a marker for early endosomes [141] . Studies in various systems have revealed multiple Rab5 GEF proteins, including RABX-5/Rabex-5 [109] , [150] , [149] , [153] , hRME-6/RME-6 [112] , and Rin2/RIN-1 [29] . RABX-5/Rabex-5 is the first protein identified as a small GTPase GEF and is primarily localized at early endosomes [52] .…”
Section: Rab5 Directs Biogenesis and Functions Of Early Endosomesmentioning
confidence: 99%
“…Given that the overactivation of Rab proteins can adversely affect endocytic trafficking, it is crucial for TBC-2, a Rab5/RAB-5 GAP, to shut down RAB-5 activity in a timely manner [22] . Zhang et al found that RAB-5 resides in discrete endosome subpopulations in the intestine of C. elegans , and under the oversight of CED-10, LET-502 synergizes with RABX-5 to revitalize RAB-5 on a subset of endosomes in the deep cytosol, ensuring the progress of basolateral recycling [150] , [149] , [153] . USP6NL/RN-tre is thought to be a GAP shared by Rab5 and Rab41, while TBC1D2/Armus/TBC-2 appears to function primarily as a GAP for Rab7 [22] , [34] .…”
Section: Rab5 Directs Biogenesis and Functions Of Early Endosomesmentioning
confidence: 99%
See 1 more Smart Citation